Benign Paroxysmal Positional Vertigo - Shahdevi Nandar; Theresa Puspanadi (Publikasi Indonesia, 2026)
Benign paroxysmal positional vertigo (BPPV) is the most common cause of vertigo. BPPV is characterized by a sudden spinning sensation along with nystagmus, triggered by specific changes in head position. BPPV most commonly occurs when otoliths are displaced into the posterior semicircular canal; therefore, the Dix–Hallpike test is used to establish the diagnosis, and the Epley maneuver is performed to reposition the otoliths as the main therapy. The prognosis is good, but recurrences and residual dizziness may occur after therapy. This article aims to provide a comprehensive understanding of BPPV, including its definition, epidemiology, etiology, pathophysiology, clinical manifestations, diagnosis, differential diagnosis, management, and prognosis. The writing of this article uses a literature-study method with a narrative approach. BPPV has a lifetime prevalence of 2.4% with an incidence of 10.7–64 cases per 100,000 people per year, is 2–3 times more frequent in women, and peaks in the fifth–sixth decades of life. The most frequent type is PC-BPPV (60–90%). Pathophysiology involves the mechanisms of canalithiasis or cupulolithiasis. The diagnosis is established through the Dix–Hallpike test for PC-BPPV and the supine roll test for LC-BPPV. The main management is the canalith repositioning procedure: the Epley maneuver for PC-BPPV and the Lempert maneuver for LC-BPPV. The prognosis is generally good, with 20–50% of patients recovering spontaneously within 1–3 months; however, a recurrence rate of 40–50% within 5 years and residual dizziness of 29.6–76.9% may occur. BPPV is the most frequent cause of vertigo with relatively simple diagnosis and management, but it is often missed. A comprehensive understanding of BPPV is important for clinicians to diagnose and manage it appropriately in order to prevent complications and improve patients’ quality of life.